MODEL FOR MONEY MULE RECRUITMENT IN MALAYSIA: AWARENESS PERSPECTIVE - Vedamanikam, Mohanamerry; Chethiyar, Saralah Devi Mariamdaran; Nasir, Norruzeyati B Che Mohd (PEOPLE: International Journal of Social Sciences, 2020)
Technology advancement has taken a new shape in leading the world into digital civilization, remarkably in e-commerce, communication, and financial sectors. Taking advantage of the technology, criminals have also digitalized their modus operandi targeting the digital society with fraud and cybercrimes, hence contributing illicit funds. To disguise the money trail to the illegal activities, illicit funds sourced from unlawful and fraudulent activities transformed into legal funds via a money-laundering scheme. Money laundering is perceived as a global threat where funds reverted to the criminal and enter a legitimate economy. To enable the criminals, maintain anonymity, and non-visible to the detection of law enforcement, money mules are positioned in the money laundering chain between actual criminal and illicit funds. Money mules are characters recruited by criminal networks to perform fund transfers by utilizing their accounts. Recruitment is done by offering a job with simple recruitment criteria and attractive income and rewards. This study will examine money mule recruitment and development of a model with related variables to establish the relationship between the aspect of job criteria awareness and the ability of the victims to detect the hidden criminal elements and exposure to law enforcement and derive into the decision to accept the job offer. In this research, both quantitative and qualitative approaches will be employed with surveys and interviews.